Motor Neuron Gene Therapy: Lessons from Spinal Muscular Atrophy for Amyotrophic Lateral Sclerosis - Tosolini, Andrew P.; Sleigh, James N. (Frontiers in Molecular Neuroscience, 2017)
Spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS) are severe nervous system diseases characterised by the degeneration of lower motor neurons. They share a number of additional pathological, cellular, and genetic parallels suggesting that mechanistic and clinical insights into one disorder may have value for the other. While there are currently no clinical ALS gene therapies, the splice-switching antisense oligonucleotide, nusinersen, was recently approved for SMA. This milestone was achieved through extensive pre-clinical research and patient trials, which together have spawned fundamental insights into motor neuron gene therapy. We have thus tried to distil key information garnered from SMA research, in the hope that it may stimulate a more directed approach to ALS gene therapy. Not only must the type of therapeutic (e.g. antisense oligonucleotide vs. viral vector) be sensibly selected, but considerable thought must be applied to the where, which, what, and when in order to enhance treatment benefit: to where (cell types and tissues) must the drug be delivered and how can this be best achieved? Which perturbed pathways must be corrected and can they be concurrently targeted? What dosing regime and concentration should be used? When should medication be administered? These questions are intuitive, but central to identifying and optimising a successful gene therapy. Providing definitive solutions to these quandaries will be difficult, but clear thinking about therapeutic testing is necessary if we are to have the best chance of developing viable ALS gene therapies and improving upon early generation SMA treatments.